(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The global COVID-19 pandemic has had a profound impact on organizations, necessitating adaptations to ensure business continuity. In light of the new normal working conditions, this study focused on examining employees’ work engagement and well-being. The theoretical framework of this study drew upon William Kahn’s (1990) work engagement theory and Diener’s (1984) theory of subjective well-being. To assess these constructs, the researcher utilized instruments developed by Pradhan and Hati (2019), Prawitz et al. (2006), Rich et al. (2010), Kuok and Taormina (2017), and May et al. (2004), which were distributed to 100 employees working in restaurants in Cagayan de Oro City. A descriptive correlational design was employed, utilizing statistical tools such as frequency, mean, percentage, and standard deviation to determine the level of work engagement and well-being. Additionally, multiple regression analysis was used to identify the factors that predict work engagement. The study’s findings revealed that employees demonstrated high levels of well-being and work engagement. Notably, the physical, mental, and emotional dimensions of well-being were the most significant predictors of work engagement. The study highlights the importance of conducting further empirical investigations to examine the impact of employees’ financial well-being on their work engagement in the new normal.